GIS-based optimization method for utilizing coal remaining resources and post-mining land use planning: A case study of PT Adaro coal mine in South Kalimantan - Mohamad Anis; Arifudin Idrus; Hendra Amijaya; Subagyo Subagyo (UPT Penerbitan Universitas Jember, 2016)
Coal is a non-renewable energy resource that has been the main source of energy and the most important in the world. Resource coal plays a strategic role in economic and social development in many industrialized countries [3, 4, 6]. Coal mining activities may cause a series of environmental and socio-economic issues in communities around the mining area. Mining can become an obstacle to environmental sustainability and a major hidden danger to the security of the local ecology [3, 4, 6]. Therefore, the coal mining industry should follow some specific principles and factors in achieving sustainable development. These factors include geological conditions, land use, mining technology, environmental sustainability policies and government regulations, socio-economic factors, as well as sustainability optimization for postmining land use. Resources of the remains of the coal which is defined as the last remaining condition of the resources and reserves of coal when the coal companies have already completed the life of the mine [1, 2, 5] or the expiration of the licensing contract (in accordance with government permission). This research uses approch of knowledge-driven GIS based methods mainly Analytical Hierarchy Process (AHP) and Fuzzy logic for utilizing coal remaining resources and post-mining land use planning. The mining area selected for this study belongs to a PKP2B (Work Agreement for Coal Mining) company named Adaro Indonesia (PT Adaro).